2019
DOI: 10.1007/s10120-019-00949-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation genome-wide analysis in remnant and primary gastric cancers

Abstract: Background Although primary (PGC) and remnant gastric cancers (RGC) both originate from the same gastrointestinal organ, they have very distinct clinicopathological behaviors. We hypothesized that there would be distinct differences in DNA methylation patterns that would occur during carcinogenesis of RGC and PGC, and that the differences in methylation patterns may help identify the primary factor contributing to chronic inflammation in patients with RGC. Methods We investigated the genome-wide DNA methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In addition to esophageal carcinoma, abnormal expression of EPB41L3 has been reported in other common digestive system cancer types, including gastric cancer, intestinal carcinoma, colorectal cancer, hepatocellular carcinoma and pancreatic carcinoma (71-75). Consistent with previous findings that Helicobacter pylori (HP)-induced inflammatory response promotes EPB41L3 DNA methylation, the methylation of EPB41L3 is significantly lower in remnant gastric cancers with the decline of HP infection following distal gastrectomy (73,74). In colorectal cancer, protein 4.1B/DAL-1 has been shown to be downregulated through membrane proteomic analysis (72).…”
Section: Meningiomas a Loss Of Protein 41b/dal-1 Occurs In ≥50%supporting
confidence: 84%
“…In addition to esophageal carcinoma, abnormal expression of EPB41L3 has been reported in other common digestive system cancer types, including gastric cancer, intestinal carcinoma, colorectal cancer, hepatocellular carcinoma and pancreatic carcinoma (71-75). Consistent with previous findings that Helicobacter pylori (HP)-induced inflammatory response promotes EPB41L3 DNA methylation, the methylation of EPB41L3 is significantly lower in remnant gastric cancers with the decline of HP infection following distal gastrectomy (73,74). In colorectal cancer, protein 4.1B/DAL-1 has been shown to be downregulated through membrane proteomic analysis (72).…”
Section: Meningiomas a Loss Of Protein 41b/dal-1 Occurs In ≥50%supporting
confidence: 84%
“…In patients with GC, previous studies have revealed that DNA methylation could serve as molecular biomarkers in helicobacter pylori infection, cancer occurrence, and prognosis (10). Meanwhile, with the rapid development of highthroughput sequencing, genome-wide profiling provides us more individualized and systematic evaluation of DNA methylation in cancer (11,12). However, the molecular mechanisms underlying gene-expression regulated by DNA methylation is unclear, and the diagnostic and prognostic value of these DNA methylation-driven gene remains to be future explored.…”
Section: Introductionmentioning
confidence: 99%
“…Due to low levels of DNA methylation, replicates for some samples had no detectable methylation, as anticipated. Methylation was quantified using the Relative Methylation Value (RMV), based on calculation of 2 -ΔΔCt for each detectable replicate compared to the mean Ct for β-actin (ACTB) (22,23). The bisulfite-modified DNA was assessed for CHFR-promoter methylation with 200 nM forward primer, 5'-GTT ATT TTC GTG ATT CGT AGG CGA C-3', 200 nM reverse primer, 5'-CGA AAC CGA AAA TAA CCC GCG-3', and 80 nM probe, 5'-\56-FAM\ CGC TCG ACC \ZEN\ ATC TTT AAT CCT AAC CAA ACG ACT TC \3IABkFQ\-3'.…”
Section: Methodsmentioning
confidence: 99%
“…For non-detectable replicates, a Ct of 100 was used to give a near zero value for 2 -ΔΔCt . The mean 2 -ΔΔCt value (RMV) was calculated as: mean 2 -ΔΔCt (RMV)=(2 -ΔΔCt_replicate_1 +2 -ΔΔCt_replicate_2 +2 -ΔΔCt_replicate_3 )/3 (22,23).…”
Section: Methodsmentioning
confidence: 99%